Caracterização de uma pescaria de pequena escala em um bairro urbano de Salvador, Bahia - Malafaia, Priscilla Nogueira e (2018)
The present study aims to identify areas and fishing effort and fishing resources captured by the artisanal handline fleet allocated in the Pituba neighborhood Salvador, Bahia - Brazil. Data were collected during the year of 2009 and 560 fish landings were monitored. A total of 96 species were recorded, being those of greater frequency of occurrence (> 15%) the Guaguanche (Sphyraena guachancho), Lane snapper (Lutjanus synagris), King mackerel (Scomberomorus cavalla), Blackfin tuna (Thunnus atlanticus), Little tunny (Euthynus alleteratus), Caribbean sharpnose shark (Rhizoprionodon porosus) and Common dolphinfish (Coryphaena hippurus). The fishing dynamics is seasonal marked by between rainy season (march to august) and dry seasons (september to march). Importantly, the fishing area used by the fishing community is the same for more than a century, being quantified the use of 42 subareas, being highlighted the Lama (35.2%) among the most visited mainly in the rainy season.